The Formation of Takzeem Keuguree Morals: A Sociological-Anthropological Approach in Aceh's Traditional Pasantren - Fahmi Arfan; Ida Hasanah; Mustafa Usman; M. Chalis; Cut Nya Dhin; Irwan; Muhammad Nur (Jurnal Serambi Ilmu, 2023)
This study aims to find out how the strategy of forming takzeem keu guree morals in traditional Islamic boarding school students in Aceh Province, the research uses a sociological-anthropological qualitative approach, the data collection tools are interviews, observation and documentation, data analysis using a comparative analysis approach, considering that there are a large number of research sites, with a comparative approach each reduced data is analyzed for similarities and differences, any data that has been compared will be easy to answer which research objectives as the basis for conclusions. The results of the study show that traditional Aceh pesantren education has succeeded in producing people with good morals who have good, extreme and acute takzeem keu guree values. Not only takzeem him but including the whole guree family, even able to survive for a long time until the end of his life.